POTENSI DAUN KAYU LUBANG (Timonius flavescens (Jacq.) Baker) SEBAGAI ALTERNATIF MENGATASI JERAWAT - Cici Nasya Nita; Rosha Kurnia Fembriyanto; Nur Annis Hidayati (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2018)
Kayu lubang are plants which one traditionally used to acne treatment. Scientifically acne is caused bacteria’s such as Propionibacterium acnes dan Staphylococcus aureus infection. The growth of Propionibacterium acnes and Staphylococcus aureus be inhibition with phytochemical compounds contained leaves of kayu lubang. The purpose of this research was to identification phytochemical compunds from rude extract ethanol leaves of kayu lubang and which consentration extract that shows the optimum to inhibition growth of Propionibacterium acnes dan Staphylococcus aureus in antibacterial activity test. Phytochemical test conducted qualitative and antibacterial activity test using disc diffusion with concentration 15%, 20%, 25%, 30%, 35% dan 40% in 3 replication. Based on the results showed that in general those leaves contain alcaloid, phenol, tannin and steroid. The optimum inhibition zone results of extract inhibition bacterial growth at concentration of 40%, inhibition zone Propionibacterium acnes inhibition zone of 6,83 mm while Staphylococcus aureus bacteria was 5,53 mm. Based on the results of statistical tests DMRT effects of extracts leaves of kayu lubang against the bacteria Propionibacterium acnes and Staphylococcus aureus showed significant differences among for 95% confidence.